2000
DOI: 10.1016/s1097-2765(00)80442-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between a Poly(A)-Specific Ribonuclease and the 5′ Cap Influences mRNA Deadenylation Rates In Vitro

Abstract: We have used an in vitro system that reproduces in vivo aspects of mRNA turnover to elucidate mechanisms of deadenylation. DAN, the major enzyme responsible for poly(A) tail shortening in vitro, specifically interacts with the 5' cap structure of RNA substrates, and this interaction is greatly stimulated by a poly(A) tail. Several observations suggest that cap-DAN interactions are functionally important for the networking between regulated mRNA stability and translation. First, uncapped RNA substrates are inef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
2
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(163 citation statements)
references
References 64 publications
4
155
2
2
Order By: Relevance
“…To test this possibility, we employed an in vitro mRNA stabilization system using HeLa cell S100 extract, which was developed by Ford et al (23). In this system, the general pathways and many of the regulatory aspects of mRNA degradation can be reproduced (18,31). The rate of both deadenylation and degradation of exogenous capped and polyadenylated RNA substrates is up-regulated by the presence of ARE in the body of the RNA substrates (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this possibility, we employed an in vitro mRNA stabilization system using HeLa cell S100 extract, which was developed by Ford et al (23). In this system, the general pathways and many of the regulatory aspects of mRNA degradation can be reproduced (18,31). The rate of both deadenylation and degradation of exogenous capped and polyadenylated RNA substrates is up-regulated by the presence of ARE in the body of the RNA substrates (23).…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme responsible for the default deadenylation upon Xenopus oocyte maturation is a deadenylase PARN/DAN (50). The human homolog of PARN has been shown to be also functional in the in vitro system that we used here (31). Recent work revealed that another deadenylase, Xenopus nocturnin, is involved in posttranscriptional control of circadian rhythm-related mRNAs (51).…”
Section: Discussionmentioning
confidence: 99%
“…However, compelling evidence suggests that PARN is a key nuclease involved in both mRNA decay (7) and mRNA poly(A) tail length control during X. laevis oocyte development (2,9). The cap interacting and poly(A) degrading properties of PARN also provide evidence that PARN may play a role in controlling initiation of protein synthesis (3, 6 -8).…”
Section: Poly(a)-specific Ribonuclease (Parn)mentioning
confidence: 99%
“…Three enzyme complexes, CCR4-NOT [4], PAN2-PAN3 [5,6] and PARN [7][8][9], have been identified as mRNA deadenylases in eukaryotic cells. CCR4-associat-npg ed factor 1 (CAF1) is a subunit of the CCR4-NOT complex, which is an evolutionarily conserved protein complex.…”
Section: Introductionmentioning
confidence: 99%